BERFIKIR KRITIS TERHADAP ARAH PEMILIHAN KARIR PADA SISWA KELAS 12 KEJURUAN PERKANTORAN DI SMK MADYA MANGGALA - Citra Retna Humaira; Windia Hadi; Fauziah Izzatun Nuha; Fatriana Sekar Ayuning Melati; Salma Aprilia Zahra; Ibnu Faqih Alfarizi; Eliana Cinta Prastiwi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This article discusses the importance of critical thinking skills in career choices for grade 12 students at SMK Madya Manggala. The results of interviews and observations show that the majority of students have made decisions regarding their careers, but there are some who are still undecided. They are also able to distinguish fact from fiction, but have difficulty distinguishing relevant ideas from irrelevant ones. Observations also show that the majority of students have planned their decisions for their next career path, but there are still some who are unsure and have not prepared well. Class 12 students' career choices and career development depend on decision-making skills theory and decision-making models. By applying critical thinking skills, it is hoped that students can improve their ability to choose an appropriate career. This abstract discusses the importance of critical thinking skills in choosing careers for grade 12 students at SMK Madya Manggala. By applying critical thinking skills, it is hoped that students can improve their ability to choose an appropriate career.